Election Risk Management during the COVID-19 Pandemic in Indonesian General Election - Rahmadhani, Marissa Laila; Oktaviyanti, Nurcahyaningrum (CV The Journal Publishing, 2023)
The 2020 Pilkada implementation leaves many problems in COVID-19 pandemic. Many election participants did not comply with health protocols. This study explains evaluation of Pilkada during pandemic. In this evaluation, extent of risk management that has been carried out and its impact will be seen. This study also describes risk management model that can be carried out in future election governance in Indonesia based on SVA. Method used in this study is a literature study using systematic review model. Results of this study indicated that there is a problem of inadequate legal umbrella in organizing elections in crisis. Increased budget added new problems due to challenging discussions between organizers and local government. Also, coordination between institutions and violations’ handling related to health protocols has not been maximized yet. Use of SVA in voting method can significantly reduce the risk of virus transmission in an outbreak or other crisis-induced risk.